Inovasi Kurikulum PAI Berbasis Pembiasaan Khitobah untuk Meningkatkan Rasa Percaya Diri Siswa di MAN 2 Karanganyar - Hanani, Hanif; Hasanah, Amalia (Darul Yasin Al Sys, 2024)
A curriculum innovation is a specific and recent idea, idea or action carried out in a curricular area. This innovation is designed to solve the problem of education. When there is a problem of the lack of self-confidence of the students of Madrasah Aliyah State 2 Karanganyar, then it is felt necessary to innovate the curriculum of Islamic Religious Education (PAI) by holding routine changes for students in turn. This method of research uses qualitative descriptive research that explains what happens in accordance with the facts on the ground. Data collection techniques are done through observation, documentation and interviews. The results of the research show that the innovation of the PAI curriculum based on the practice of chitobah runs well and has a positive impact on students. Chitobah is running on schedule, although there are some obstacles, but there can be solutions.